Uji Aktivitas Antioksidan Ekstrak Etanol Daging Buah Asam (Tamarindus indica L.) Asal Kota Bima Nusa Tenggara Barat Dengan Metode DPPH - Imrawati, Muzakkir Baitz, Mar’atun Jannah (Jurnal Farmasi dan Ilmu Pengobatan, 2016)
Antioxidant are compounds neutralizing free radicals. Based on the previous research, in the flesh of tamarind fruit contains flavonoids that act as antioxidant. This research aimed to determine the antioxidant activity on the extract of tamarind fruit flesh (Tamarindus indica L). Antioxidant activity was done using the reduction method of free radicals by DPPH (1,1- DiPhenyl-2-Picryl Hidrazil). Antioxidant assay of the tamarind fruit flesh extract was measured using UV-VIS Spectrophotometer at the maximum wavelength 0f 515,23 nm with various concentrations of 50, 100, 200, 250 and 300 ppm. The comparison used was quercetin with concentrations of 1, 2, 3 and 5 ppm. The calculation showed that the tamarind fruit flesh has antioxidant activity with IC50 values 740,833 µg/mL and the quercetin has IC50 values 1,045 µg/mL.